Maternal abdominal subcutaneous fat thickness as a predictor for adverse pregnancy outcome: a longitudinal cohort study. (January 2016) - Kennedy, NJ; Peek, MJ; Quinton, AE; Lanzarone, V; Martin, A; Benzie, R; Nanan, R
Abstract : Objective: To assess maternal abdominal subcutaneous fat thickness (SFT) measured by ultrasound as an independent predictor of adverse pregnancy outcomes. Design: A prospective longitudinal cohort study performed on pregnancies delivered between 2012 and 2014. Setting: Sydney, Australia. Population: About 1510 pregnant women attending routine obstetric ultrasounds. Methods: Maternal SFT was measured on routine ultrasounds at 11–14 weeks' gestation (SFT1) and 18–22 weeks' gestation (SFT2). SFT measurements were assessed for estimating risks for obesity‐related pregnancy outcomes using logistic regression modelling adjusted for maternal age, parity, smoking status and body mass index (BMI). Main outcome measures: Hypertensive disease, gestational diabetes, caesarean section, low birthweight, preterm delivery, neonatal respiratory distress, Apgar scores, and admission to a neonatal intensive care unit. Results: SFT1 and SFT2 were measured on 1461 and 1363 women, respectively. Mean thickness (range) were 21.2 mm (6.9–73.9) for SFT1 and 20.3 mm (7.5–68.0) for SFT2. Complete outcome data were available for 1385 pregnancies. In all, 54% of the women were overweight/obese. The SFT measures decreased from early to mid‐pregnancy in overweight/obese women. There was moderate correlation between BMI and SFT1 ( R 2 = 0.56) and BMI and SFT2 ( R 2 = 0.55). In a multivariate model, SFT1 and SFT2 were better predictors for adverse pregnancy outcomes than BMI. Conclusion: Maternal SFT is a significant independent predictor of adverse pregnancy outcomes. Incorporation of SFT into future models for adverse pregnancy outcome may prove valuable. Tweetable abstract: Maternal abdominal ultrasound fat thickness measurement predicts adverse pregnancy outcomes. Tweetable abstract: Maternal abdominal ultrasound fat thickness measurement predicts adverse pregnancy outcomes.